Lo-on a focus on the perception of the residents of Alangalang, Leyte regarding the "practice" - Pedrera, Gay Anne G.; Saulog, Dianne Stephanie B. (2003)
Many people subject themselves to traditional medicine practices such as lo-on for reasons like poverty, lack of medicine, health and medical services particularly in remote areas, ignorance or hopelessness, or because they develop some kind of affinity with traditional medicine practitioners which they may not have with a Western practitioner. Whatever the reason is to cater to traditional medicine practices.
Despite the modernization and the existence of medical health centers, the prevalence of traditional medicine practices such as lo-on still exist not only in remote areas but also in areas where accessibility to modern services are available. Hence, the conduct of the study on the perception of the residents regarding the traditional practice, lo-on in particular.
Through purposive sampling, three barangays of Alangalang, Leyte were chosen as research area because of the accessibility and prevalence of lo-on practice in the community. Twenty residents coming from the three barangays of Alangalang were chosen as respondents with ages ranging to forty (40) and above from both sexes.
Interview and pagtatanung-tanong were the methods used in gathering data that are applicable and appropriate in this kind of Study.
The aim of the study was to determine the opinion, understanding and attitudes of the residents towards the lo-on practice.
Specifically, the aim of this tudy was to find answers for questions like what is lo-on; what are its processes, rituals, and oracions; who are the people who believe in lo-on; and how do they view lo-on. Finally, what are the influencing factors or the reasons of the people to believe in lo-on.
The researchers believe that many will benefit from this study. To think that this is an indigenous one and there are still no enough studies available, the present study would be an additional resource material and would serve as a baseline for further studies and reference for future researchers.
Results of the study showed that there were different perceptions of the residents towards lo-on practice.
A Research paper.
Keywords: Filipino psychology